Phosphatidylinositol 3, 5‐Bisphosphate‐Rich Membrane Domains in Endosomes and Lysosomes. (9th December 2015) - Takatori, Sho; Tatematsu, Tsuyako; Cheng, Jinglei; Matsumoto, Jun; Akano, Takuya; Fujimoto, Toyoshi
Abstract : Phosphatidylinositol 3, 5‐bisphosphate (PtdIns(3, 5)P2 ) is a minor phospholipid but it has critical functions in endosomes/lysosomes, and its deficiency is linked to neurodegenerative diseases including amyotrophic lateral sclerosis. Using a new electron microscopic method to define the nanolevel distribution, PtdIns(3, 5)P2 was found to have a biased distribution in yeast vacuoles exposed to high salt stress and in mammalian endosomes with tubulo‐vesicular morphology. Segregation of PtdIns(3, 5)P2 ‐rich and ‐deficient domains should be important in understanding endosome/lysosome functionality. Abstract : Phosphatidylinositol 3, 5‐bisphosphate (PtdIns(3, 5)P2 ) has critical functions in endosomes and lysosomes. We developed a method to define nanoscale distribution of PtdIns(3, 5)P2 using freeze‐fracture electron microscopy. GST‐ATG18‐4×FLAG was used to label PtdIns(3, 5)P2 and its binding to phosphatidylinositol 3‐phosphate (PtdIns(3)P) was blocked by an excess of the p40 phox PX domain. In yeast exposed to hyperosmotic stress, PtdIns(3, 5)P2 was concentrated in intramembrane particle (IMP)‐deficient domains in the vacuolar membrane, which made close contact with adjacent membranes. The IMP‐deficient domain was also enriched with PtdIns(3)P, but was deficient in Vph1p, a liquid‐disordered domain marker. In yeast lacking either PtdIns(3, 5)P2 or its effector, Atg18p, the IMP‐deficient, PtdIns(3)P‐rich membranes were folded tightly to make abnormal tubular structures, thus showing where the vacuolar fragmentation process is arrested when PtdIns(3, 5)P2 metabolism is defective. In HeLa cells, PtdIns(3, 5)P2 was significantly enriched in the vesicular domain of RAB5‐ and RAB7‐positive endosome/lysosomes of the tubulo‐vesicular morphology. This biased distribution of PtdIns(3, 5)P2 was also observed using fluorescence microscopy, which further showed enrichment of a retromer component, VPS35, in the tubular domain. This is the first report to show segregation of PtdIns(3, 5)P2 ‐rich and ‐deficient domains in endosome/lysosomes, which should be important for endosome/lysosome functionality.